Dialog Sunni-Syi‘ah antara Konfrontasi dan Rekonsiliasi - Syamsuddin Arif (Universitas Darussalam Gontor, 2019)
AbstractSunni-Shiite relations have been a perennial problem for Muslims for hundreds of years. Each has its own characteristics, style, character, worldview and belief system. Harmony and tension continue alternately to color the relationship between the two. In the present-day Middle East, Sunni-Shia tensions contribute to multiple flash points that are viewed as growing threats to international peace and security. Many ask, therefore: Is it possible for Sunnis and Shiites to be reconciled or united? Is it possible that the centuries-old conflict is revoked and eliminated? This article tries to answer these crucial questions from theological and historical perspectives, revealing facts that are often overlooked and tracing primary and secondary authoritative sources. It was concluded that the Shiites emerged from within the Muslim community and had freely but persistently used Islamic concepts, terms, and symbols such as imam, Ahlul Bayt, ‘Ashura (the tenth day of Muharram), mut‘ah (temporary marriage), sayyid (master), ayat (sign) for ideological purposes most of which contradict the faith of Ahlus Sunnah wal Jama‘ah.Keywords: Shi'ah, Shiism, Sunni-Shia Conflict, Intra-religious Polemic, Sectarianism, ReconciliationAbstrakHubungan Sunni-Syi‘ah menjadi masalah perenial umat Islam sejak beratus tahun lamanya. Masing-masing mempunyai ciri, corak, karakter, cara pandang dan sistem kepercayaan tersendiri. Kerukunan dan ketegangan silih-berganti mewarnai relasi antara keduanya. Banyak yang bertanya, mungkinkah Sunni dan Syi‘ah dipertemukan atau dipersatukan? Dan mungkinkah konflik yang telah mengakar ratusan tahun lamanya itu bisa dicabut dan dilenyapkan? Artikel ini coba menjawab pertanyaan-pertanyaan krusial ini dari perspektif teologis maupun historis, dengan menyingkap fakta-fakta yang sering diabaikan dan menelusuri sumber-sumber otoritatif primer serta sekunder. Disimpulkan bahwa Syi‘ah muncul dari dalam umat Islam dan memakai konsep-konsep, istilah-istilah, serta simbol-simbol yang ada di dalam Islam seperti ‘imam’, ‘Ahlul Bayt’, ‘Asyura’, ‘mut‘ah’, ‘sayyid’, ‘ayat’ untuk kepentingan ideologis yang bertolak-belakang dengan akidah Ahlus Sunnah wal Jama‘ah. Kata Kunci: Syiah, Konflik Sunni-Syiah, Polemik Antargolongan, Sektarianisme,Rekonsiliasi.